Devalued and Distrusted : Can the Pharmaceutical Industry Restore Its Broken Image? - LaMattina, John L. (Hoboken, New Jersey : Wiley, 2013)
"While the pharmaceutical industry can play an important role in converting the knowledge generated by the Human Genome Project into new medicines, it also faces a popular perception that it is simply out to make money by promoting unsafe medicines to an unsuspecting public. Written by former Pfizer president John LaMattina, this book addresses the progress that the industry has made in improving its abilities to measure both the risk and benefits of its new medicines, where the industry should invest its R & D resources, and how the industry can rehabilitate its image. Essential reading for pharmaceutical executives and professionals"--
1. The four secrets the drug companies don't want you to know -- 2. What has happened to R & D productivity? -- 3. Key therapeutic areas for improving health -- 4. Improving R & D output -- 5. Restoring pharma's image -- 6. Final thoughts.
Includes index.
Machine generated contents note: Introduction Part 1. "The 4 secrets that drug companies don't want you to know" part 2. What has happened to R & D productivity? a. impact of mergers b. impact of FDA c. impact of payers Part 3. Challenges in key therapeutic areas for improving health a. cancer b. diseases of the brain c. cardiovascular disease d. diabetes e. bacterial Infections part 4. Improving R & D output a. view of others b. personal vision part 5. Restoring the pharma image part 6. Final thoughts.
Includes bibliographical references and index.
Print version record.
Keywords: Pharmaceutical industry -- Corrupt practices; Medical; MEDICAL -- Pharmacology; Pharmaceutical industry -- Corrupt practices; Electronic books